Peran Guru BK dalam Membantu Santri Mengatasi Masalah Akademik - Reza Muttaqin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
The role of Guidance and Counselling Teachers (BK) is very important in the world of education, especially in helping students overcome academic problems. Students often face various challenges that can affect their learning achievement, including social pressure, personal problems, and difficulties in understanding the subject matter. This study aims to explore the role and strategies used by the counselling teachers in supporting santri in overcoming their academic problems. Through a qualitative approach, data were collected through interviews with counselling teachers and santri in several pesantren. The results show that appropriate interventions from counselling teachers can improve the learning motivation and academic performance of santri.